Две судьбы-2: [романы] / Семен Малков - Малков Семен Наумович (Гелиос, 2003)
Экземпляры: ф.14 (ретро) / Инвентарный номер: 49974 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М 19 / ББК: 84(2Рос=Рус)6